Blogging to drive business : create and maintain valuable customer connections - Butow, Eric (Que, 2013)
BLOGGING TO DRIVE BUSINESS USE BLOGGING TO SUPERCHARGE SALES, CUSTOMER LOYALTY, INNOVATION, AND PROFITS Blogging can help you deepen customer loyalty, reach new customers, gain indispensable feedback, and drive more sales. This no-nonsense guide shows how to craft a business blog that does all that, and more--building your business and increasing your profits. Top e-marketers and business bloggers Eric Butow and Rebecca Bollwitt help you define clear goals, generate the right content with the right tools, attract visitors, build communities, and avoid costly mistakes. They draw on their own extensive experience, as well as the work of innovators from companies such as Intel, Starbucks, ING Direct, Procter & Gamble, and Tumblr. WHATEVER YOUR ROLE IN THE BUSINESS, YOU'LL LEARN HOW TO: Launch a blog that truly represents the best of your business Create a comprehensive, long-term blogging strategy to maximize the return on investment (ROI) from your blog Staff your blogging initiative Integrate blogs with other offline and online marketing programs, including social networking websites Use your blog to drive customers and prospects to the business Push up-to-the-minute information to customers via RSS Build a thriving online community--and learn from what it tells you Manage comments (and decide whether to have them) Operate successful contests and sweepstakes campaigns on your blog Utilize podcasts, vlogs, microblogging, and other new techniques Gain business value from hot new Web 3.0 technologies, including widgets, mashups, personal agents, and the Semantic Web Track your blog performance, spot and respond to trends, and translate and report data you receive from your blog.